A validade da cláusula compromissória arbitral nos contratos de bill of lading - Gimenes, Maria Carolina Caseira (2018)
The study aims to analyze the validity of the arbitration arbitration clause bill of lading, or in the Bill of Lading (BL) whose contractual insertion arises from the customary collation of this mercantile sphere. In Brazil, the understanding is that the relationship between shipowner and shipper is a relation of consumption, with this, the Maximalist Theory positions itself by the invalidity of the arbitration clause in the BL, since it contract, and, if it deals with consumeirista pacts, such clause would be abusive International maritime transport is instrumented by the type that customary practice in the middle, so that standard clauses are consolidation of the desirable negotiation to such activity customary, in favor of all the authors who participate in the mercantile expedition. With this, the election of the arbitration channel, are reflexes of the praxes of the commerce international law, so that, unlike the majority Brazil, there is no favoring of shipowners or shippers with the adoption of arbitration arbitration clause. Some judges, even contradicting the position majority, removed the consumer relationship between the contracting parties of the BL, since there is no vulnerability, stating that the BL is not an adhesion contract and, therefore, if stamped in the bill of lading, the Brazilian forum is party to the dispute, since the arbitration clause is valid and the arbitration clause isArbitral Tribunal convened competent to judge what happened. It is concluded that,even if they understand the BL as an instrument of accession, the clause arbitration agreement is valid, the Arbitration Law provides that it is possible to insertion of an arbitration clause into contracts of an adhesive nature.